The Factors that Induce or Overcome Freezing of Gait in Parkinson’s Disease - S. Rahman; H. J. Griffin; N. P. Quinn; M. Jahanshahi (Behavioural Neurology)
Freezing of gait (FoG), a transient halt in walking, is a major mobility problem for patients with Parkinson’s disease (PD). This study examined the factors that induce FoG, and identified the cues and strategies that help overcome it through a postal survey of 130 PD patients. 72% reported FoG. The factors that commonly induced FoG were turning, fatigue, confined spaces and stressful situations, in addition to emotional factors. FoG was also ameliorated by various attentional and external cueing strategies. The concept of paradoxical kinesis, the potential neural substrates of such external cueing effects, and their importance for rehabilitation in PD are discussed.